22. Slovenski slavistični kongres, Slavistika v regijah: Maribor, Univerza v Mariboru, 29. 9.–1. 10. 2011 - Valh Lopert, Alenka; Zemljak Jontes, Melita (Slavia Centralis, 2020)
The authors report on the 22nd Slovenian Slavic Congress, which took place from 29 September to 1 October 2011 in Maribor.
Keywords: report; Slovenian Slavic Congress; Slavic Studies in the Regions; Maribor; kongress; Slavic studies; Slovenian